Care to terminal patients. Perception of nurses from the intensive care unit of a hospital - Camila Mussolin Tamaki; Silmara Meneguin; Rubia Aguiar Alencar; Claudia Helena Bronzatto Luppi (Universidad de Antioquia, 2014)
Objective. To identify the perception of nurses with regard to the process of providing care to patients in the context of hospice care. Method. Qualitative study using the methodological framework Collective Subject Discourse. A total of 18 nursing professionals of the adult intensive care unit of a public hospital in São Paulo, Brazil were interviewed between June and August 2012. Results. The process of providing care to terminal patients is permeated by negative, conflictive and mixed feelings. As regards communication, while the participants acknowledge its importance as a therapeutic resource, they also admit a lack of professional qualification. Conclusion. The interviewees have difficulties to deal with care provided to terminal patients. The qualification of these professionals needs to be improved, starting in the undergraduate program.